Impacted Maxillary Fourth Molars (A Case Report) - Meliha Rübendüz (Galenos Yayinevi, 1997)
Lateral, Postero-anterior and orthopantomographic radiograms are mostly needed diagnostic materials in determining the skeletal discrepancies. However, no mathematical rule is evident in the biological milieu. Generally, as the impaction of the third molars are frequently incidental, the radiographic images of the germs of these teeth are especially required. The determination of the existence of these teeth causes no problem at the end of mixed dentition and can easily be seen on the radiograms. It is aimed to introduce a case with impacted maxillary fourth molar, which has 0.12% incidence. However, it may be useful to state that every case might not be adult as reported in this paper and there-fore these teeth could not be seen on the radiograprams due to insufficient calcification.